Cacat Formil Penetapan Tersangka oleh KPK: Analisis Yuridis atas Pelanggaran Due Process of Law dalam Perkara Gus Yaqut - Wiratmadinata; Hanri Aldino; Radhali (Jurnal Hukum Samudra Keadilan, 2026)
This study aims to analyze the legality of suspect designation by the Corruption Eradication Commission (KPK) from the perspective of criminal procedural law, with a focus on procedural (formal) aspects and their juridical implications. The main issue lies in the alleged procedural defects in the suspect designation, which potentially violate the principle of due process of law. This research employs a normative legal method with statutory, conceptual, and case approaches. Legal materials are analyzed qualitatively using a deductive-inductive method. The findings reveal that the suspect designation in the case at hand contains several fundamental procedural defects, including premature designation without sufficient evidence, abuse of authority (ultra vires), administrative procedural violations, inconsistency of legal basis, and the use of documents that do not qualify as lawful evidence under the Criminal Procedure Code. These defects cumulatively render the designation legally invalid. The juridical implication is that the suspect designation becomes null and void, thereby invalidating all subsequent legal processes derived from it. This study underscores the importance of strict adherence to legal procedures as a mechanism to safeguard human rights and prevent abuse of power in law enforcement